Sherlock holmes : baker street irregulars - Doyle, Arthur Conan, Sir, 1859-1930.; Vogel, Malvina G.; Lynch, Brendan (Edina, Minn. : ABDO Pub., 2006)
Includes three Sherlock Holmes mystery adventures: "The Red-headed League," "The Adventure of the Speckled Band," and "The Adventure of the Copper Beeches."
Originally published: New York : Playmore : Waldman Pub., 1992.
Keywords: Detective and mystery stories, English; Children's stories, English; Mystery and detective stories; Short stories